A short-term efficacy comparison between the FNS and THA as interventions for unstable femoral neck fracture - Si, Kunpeng; Zhang, Yuelei; Wang, Gang (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to compare the difference in short-term clinical effects of internal fixation using the femoral neck system (FNS) and total hip arthroplasty (THA) on unstable femoral neck fractures.MethodsA retrospective analysis was conducted on 37 cases of unstable femoral neck fracture admitted to our hospital from 1 July 2020 to 30 June 2023. The cases were divided into an FNS group (21 cases) and a THA group (16 cases) based on the surgical method used. A comparative analysis was performed between the cohorts regarding demographic characteristics (sex and age), perioperative parameters (length of hospital stay, surgical duration, and intraoperative blood loss), and postoperative functional outcomes [Visual Analog Pain Score (VAS) and Harris Hip Score (HHS) assessments].ResultThe operative time, length of hospital stay, and intraoperative blood loss in the FNS group were significantly lower than those in the THA group, and the time of weight bearing on the ground in the FNS group was significantly longer than that in the THA group (P < 0.01). The comparative analysis revealed comparable outcomes in postoperative pain intensity (VAS) and functional recovery (HHS) between the cohorts, with both parameters demonstrating statistically equivalent values (P > 0.05).ConclusionFor unstable femoral neck fractures, FNS and THA were equally effective. Although shortening and necrosis were observed in the FNS group, no statistically significant difference in postoperative complications was found between the two groups. The operative time of FNS was shorter, with less intraoperative bleeding. However, the earlier weight-bearing time of THA was more conducive to the recovery of limb function.